Níveis proteicos nos índices produtivos e reprodutivos do acará bandeira (Pterophyllum scalare) - Matielo, Marcelo Darós (2014)
The angel fish, Pterophyllum scalare, is an Amazonian fish of great demand in the market and easy in production, but there are few nutritional studies for matrices of this specie. The objective of the project was to assess the supply of rations , with different protein levels, to evaluate the influence ofproduction index and reproductive parameters of angel fish in the laboratory . The experiment was conducted at the Federal Institute of Espirito Santo in the period January 12th to June 18th of 2013 . The design was a completerandomized block design withfive treatments (22.5, 24.5, 26.5, 28.5, 30.5% crude protein) and five blocks performed in time. It was used the number of 25 couples (average weight of females8.78 ± 1.74g average weight of males 11.10 ± 2.62g) with the feeding lasting 60 days in each block .It was analyzed reproductive parameters; Productive parameters with performance; and histological parameters of intestinal villi. The data was analyzed for their normality by the Shapiro-Wilks test and subsequently it was performed the overall ANOVA followed by Tukey test at 5 % probability using SAEG 9.0. It was observed statistical differences in the total egg production, spawning number, weight gain of the matrices and height of intestinal villi. The number of eggs per spawning, parameters leftovereggs and larvae and measurement of the internal organs showed no difference between treatments. The highest levels showed better productivity, and the 30.5 % crude protein is the most indicated for nutrition of angel fish in reproduction